Small Klebsiella pneumoniae Plasmids: Neglected Contributors to Antibiotic Resistance - Ramirez, Maria S.; Iriarte, Andrés; Reyes-Lamothe, Rodrigo; Sherratt, David J.; Tolmasky, Marcelo E. (Frontiers in Microbiology, 2019)
Klebsiella pneumoniae is the causative agent of community- and, more commonly, hospital-acquired infections. Infections caused by this bacterium have recently become more dangerous due to the acquisition of multiresistance to antibiotics and the rise of hypervirulent variants. Plasmids usually carry genes coding for resistance to antibiotics or virulence factors, and the recent sequence of complete K. pneumoniae genomes showed that most strains harbor many of them. Unlike large plasmids, small, usually high copy number plasmids, did not attract much attention. However, these plasmids may include genes coding for specialized functions, such as antibiotic resistance, that can be expressed at high levels due to gene dosage effect. These genes may be part of mobile elements that not only facilitate their dissemination but also participate in plasmid evolution. Furthermore, high copy number plasmids may also play a role in evolution by allowing coexistence of mutated and non-mutated versions of a gene, which helps to circumvent the constraints imposed by trade-offs after certain genes mutate. Most K. pneumoniae plasmids 25-kb or smaller replicate by the ColE1-type mechanism and many of them are mobilizable. The transposon Tn1331 and derivatives were found in a high percentage of these plasmids. Another transposon that was found in representatives of this group is the blaKPC-containing Tn4401. Common resistance determinants found in these plasmids were aac(6′)-Ib and genes coding for β-lactamases including carbapenemases.